Innovation & Imitation For Nations the technological gap shock and nations' urge to imitate and copycat - Ahmad, Mohammed (Independently published, 2022)
A journey for readers through thousands of years extending from the innovation of silk & porcelain in China and paper & kohl in Pharaonic Egypt to the modern innovations in Europe and USA. This book introduces a summary of experiences for innovative nations through history. Imitation, copycatting, and knocking-off are the code that nations use as a response to the shock of ?technological gap? before embarking on innovation.
Keywords: Innovation